The association of haplotypes in IGFBP-3 gene promoter region and tissue expressions in three pig breeds. Issue 6 (1st November 2016) - Wu, Qingyan; Yu, Hao; Fang, Xibi; Cheng, Yunyun; Dong, Lijie; Wei, Wenzhen; Wang, Gang; Fu, Haoyu; Liu, Songcai; Hao, Linlin
ABSTRACT: Bama Xiang pig (BM) and Tibetan mini-pig (TM) are used as experimental animals in China; however, the dwarf molecular mechanisms of these Chinese local pig breeds are unknown. IGFBP-3 affects animal growth, carcass and meat quality. The aim of this study was to identify the polymorphisms in the promoter of the IGFBP-3 and analyse their effect on the IGFBP-3 mRNA expression level in liver and muscle tissues. High-density single-nucleotide polymorphisms (SNPs) (31) and InDels (5) were detected in the promoter of the IGFBP-3 in the BM, TM and Junmu No. 1 White (JM, control) pig breeds from 114 individuals by re-sequencing. A perfect Linkage disequilibrium consisted of 13 SNPs was observed in the promoter region and 2 main haplotypes were identified, of which the h1 genotype (GCA-ATGTACATAT) was more prevalent in JM breed than in TM or BM breeds ( P  < .0001), h2 (ATGTGCACG--CGC) was the dominant haplotype in TM and BM breeds ( P  < .0001). Expression analysis showed that haplotype of the promoter region is highly associated with the IGFBP-3 mRNA expression level in liver and muscle tissues of pigs. The IGFBP-3 mRNA expression level was determined higher in the liver and muscle tissues of pigs with h2 genotype as compared to that in pigs with h1 genotype ( P  < .05). The results suggest that the SNPs and haplotypes in the promoter of the IGFBP-3 gene may serve as useful molecular markers for the body growth traits and the breeding in swine.